Conservation and role of electrostatics in thymidylate synthase - Garg, Divita; Wade, Rebecca C. (Scientific reports, 2015)
Conservation of function across families of orthologous enzymes is generally accompanied by conservation of their active site electrostatic potentials. To study the electrostatic conservation in the highly conserved essential enzyme, thymidylate synthase (TS), we conducted a systematic species-based comparison of the electrostatic potential in the vicinity of its active site. Whereas the electrostatics of the active site of TS are generally well conserved, the TSs from minimal organisms do not conform to the overall trend. Since the genomes of minimal organisms have a high thymidine content compared to other organisms, the observation of non-conserved electrostatics was surprising. Analysis of the symbiotic relationship between minimal organisms and their hosts and the genetic completeness of the thymidine synthesis pathway suggested that TS from the minimal organism Wigglesworthia glossinidia (W.g.b.) must be active. Four residues in the vicinity of the active site of Escherichia coli TS were mutated individually and simultaneously to mimic the electrostatics of W.g.b TS. The measured activities of the E. coli TS mutants imply that conservation of electrostatics in the region of the active site is important for the activity of TS and suggest that the W.g.b. TS has the minimal activity necessary to support replication of its reduced genome.
Gesehen am 09.08.2021